Application of Fractions of Crop Evapotranspiration Affects Carbon Partitioning of Grapevine Differentially in a Hot Climate - Torres, Nazareth; Yu, Runze; Martínez-Lüscher, Johann; Kostaki, Evmorfia; Kurtural, Sahap Kaan (Frontiers in Plant Science, 2021)
Majority of viticulture regions are located in mid-latitudes characterized by weather variability and stressful environments relying on irrigation for mitigating environmental stress during the growing season and to ensure a profitable yield. The aim of this study was to characterize the response of grapevine (Vitis vinifera L. cv. Cabernet Sauvignon) to different applied water amounts based on the replacement of fractions of crop evapotranspiration (ETc) during two growing seasons with contrasting precipitation patterns. The experiment consisted of three irrigation treatments based on the weekly replacement of 25%, 50% and 100% of ETc. Grapevine stem water potential decreased during the growing season reaching its lowest value (-1.5 and -1.2 MPa, respectively) at harvest in the more stressed vines (25% and 50% ETc). Leaf gas exchange variables were measured during the two seasons and 100% ETc had the highest rates of photosynthesis, stomatal conductance and better instantaneous water use efficiency; also resulting in higher leaf chlorophyll and carotenoid content. Mineral nutrient content for nitrogen and potassium increased linearly with the increase in applied water. At harvest, no differences were observed in the number of clusters per vine; however, the 25% ETc had the lowest berry size and yield per vine with no difference in sugar content of berry. Conversely, sugar allocation to reserve organs was highly affected by applied water leading to different shoot to root biomass partitioning where shoot:root ratio, leaf non-structural carbohydrates, and photosynthetic pigments increased with greater applied water. Likewise sucrose:N ratio and root non-structural carbohydrates decreased with the lower applied water. Altogether, carbon allocation between source and sink organs likely controlled the response of grapevines to water deficits in a hot climate, and replacing 50% ETc was sufficient to sustain the grapevine performance given the enhancement of sugar transport, that could slow down the detrimental effect of water deficits on yield.